Social Well-Being in the Philippines: Indicators and Patterns - Porio, Emma E (Archīum Ateneo, 2017)
This paper describes the patterns and correlates of social well-being in the Philippines. Based on a national survey of 1200 households, the study found that: 1) most Filipinos are happy and satisfied with their current life but those outside of Metro Manila have higher levels of happiness and life satisfaction, 2) slightly more than half are not satisfied with their employment, job security, and finances but have much higher levels of satisfaction with their family/married life, relationship with friends/neighbors and amount of time they have; 3) Metro Manilans compared to their regional counterparts are less happy about their residence, usage of time, hobbies and personal health. Overall, the major components of social well-being among Filipinos are: job and finance, family life and relationships and spare time and hobbies. With regards to fairness of treatment of people from different social categories, the farther they are from Manila, they feel different groups are treated more fairly. When queried about their social capital/trust networks, most of them trusted highly their family and relatives, less with neighbors, co-workers, local government, and the police. Interestingly, their trust of secondary institutions such as hospitals and local governments increases during and after disasters. While bonding social capital (with primary groups) seem high in everyday life, bridging and linking social capital with institutions become important in post-disaster situations.